Economic Resilience and Welfare of Older Adults after the Paitua Assistance Program - Ramli, Umar; Nikmatul Ula, Siti Nurul; Rumaday, Saleman; Nurlela, Andi; Rais, Lukman (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2025)
Older adults in Southwest Papua are increasingly vulnerable both socially and economically, while the Paitua Program as a social safety net has not been empirically assessed. This study establishes a baseline evaluation using an Explanatory Sequential Mixed Methods design, combining quantitative and qualitative approaches. Data were collected from 270 elderly respondents and five informants through questionnaires, interviews, observation, and document review. Quantitative data were analyzed with descriptive and inferential statistics, while qualitative findings were examined through thematic-phenomenological analysis. Results reveal that the Paitua Program influences elderly well-being across economic, social, and psychological dimensions. The program not only addresses basic needs but also reduces family burdens, enhances security, and improves selfworth. Average scores were 2.88 for satisfaction, 3.09 for economic resilience, and 2.81 for overall well-being. Hypothesis testing confirmed significant positive effects both partially (t-test: well-being = 17.929; economic resilience = 3.970 > t-table 1.650) and simultaneously (f-test = 257.887 > f-table 3.029). The novelty of this study highlights that direct cash transfers strengthen not only economic resilience but also social and psychological well-being, an area rarely emphasized in prior research.